Pelaksanaan Inisiasi Menyusu Dini (IMD) Pada Ibu Bersalin di Pondok Bersalin Kelurahan Kolpajung - Fritria Dwi Anggraini; Layla Imroatu Zulaikha (SAKTI BIDADARI (Satuan Bakti Bidan Untuk Negeri), 2022)
Early initiation of breastfeeding (IMD) is a way to give babies the opportunity to find and suck their own breast milk. in the first hour of early life. With the presence of IMD there will be skin contact between mother and baby and also baby licking on the nipples, thereby stimulating the release of the hormone oxytocin. However, the implementation has not yet been fully implemented. Based on the preliminary study, there were 7 (70%) women giving birth who had not done IMD. Several factors that influence it are the mother's age, knowledge, and parity. The purpose of this study was to determine the implementation of early initiation of breastfeeding (IMD). This research is descriptive. Based on the timing of this study using a cross-sectional approach. The population is 30 mothers with total sampling technique. Data collection techniques using partographs. Based on the cross tabulation, it was found that 23 respondents mostly did IMD (76.7%). Meanwhile, of the other 7 respondents, a small portion did not do IMD (23.3%). From the analysis of the data above, it was found that there were still pregnant women who did not do IMD. In conclusion, there are still mothers who do not do IMD. Involving various parties is an effort that can be implemented, including moral support from families, and health workers by providing basic childbirth care with the implementation of IMD and the mother giving birth itself through physical and mental readiness.